TERMORREGULATION DURING EXERCISE: POSSIBLE DIFFERENCES AND PRIVATE NEEDS IN WOMEN(*) (Fiep Bulletin - online, 2014)
(*) Research accomplished inside of the ethical norms foreseen in the Resolution no.. 196, of October 10, 1996, of National Council of Health. The termorregulatory answer to the physical exercise promotes organic modifications that can be harmful the health and to the sporting acting. This study has the objective of lifting some subjects about the possible specific needs of water and electrolytes replacement in women. In a session of exercises, seven men and seven women had his/her corporal weight measured before and after the activity and their compared results. The maximum consumption of O2 (VO2máx) in men and women was 42mlO2/Kg/min (+ 5,8) and 30,7mlO2 / Kg / min (+ 2,3), respectively. The loss of weight corporal (PPC) average for men and women was 328,5g and 42,8g with standard deviation of 275,1 and 127,2, respectively. The difference among medium PPC was of 232,3 and it was out of the certain trust interval. The relationship between corporal weight and PPC didn't show influence in the individuals tax perspiration. The main observed difference was smallest PPC in women after the accomplishment of the exercises.
Keywords: Exercises; dehydration; sex difference